Meta-analysis of the influence of surgical margin and adjuvant radiotherapy on local recurrence after resection of sporadic desmoid-type fibromatosis. Issue 4 (15th February 2017) - Janssen, M L; van Broekhoven, D L M; Cates, J M M; Bramer, W M; Nuyttens, J J; Gronchi, A; Salas, S; Bonvalot, S; Grünhagen, D J; Verhoef, C
Abstract: Background: Extra-abdominal desmoid-type fibromatosis (DF) is a rare, locally aggressive neoplasm that is usually managed conservatively. When treatment is indicated, it typically involves surgical resection, possibly with adjuvant radiotherapy. The indications for postoperative radiotherapy and its effectiveness are unclear. The objective of this study was to estimate the effect of surgical resection margins and adjuvant radiotherapy on rates of recurrence of DF. Methods: Literature published between 1999 and 2015 was extracted from MEDLINE, Embase, Cochrane Central Registry of Trials, Web of Science and Google Scholar. Recurrence rate was analysed by meta-analysis and compared between subgroups. Results: Sixteen reports were included, consisting of a total of 1295 patients with DF. In patients treated by surgical resection alone, the risk of local recurrence was almost twofold higher for those with microscopically positive resection margins (risk ratio (RR) 1·78, 95 per cent c.i. 1·40 to 2·26). Adjuvant radiotherapy after surgery with negative margins had no detectable benefit on recurrence. In contrast, after incomplete surgical resection, adjuvant radiotherapy improved recurrence rates both in patients with primary tumours (RR 1·54, 1·05 to 2·27) and in those with recurrent DF (RR 1·60, 1·12 to 2·28). Conclusion: DF resected with microscopically positive margins has a higher risk of recurrence. Adjuvant radiotherapy appears to reduce the risk of recurrence after incomplete surgical resection, particularly in patients with recurrent tumours. Abstract : Radiotherapy after surgery for recurrence only